Studies on flow stress behaviour prediction of AZ31B alloy: Microstructural evolution and fracture mechanism - Aarjoo Jaimin; Nitin Kotkunde; Swadesh Kumar Singh; Kuldeep Kumar Saxena (Journal of Materials Research and Technology, 2023)
The hot tensile flow behaviour of the AZ31B alloy is investigated at various varying deformation temperatures (200–350 °C) and strain rates (0.1s−1, 0.01s−1, and 0.001s−1). The deformation condition significantly influenced the mechanical properties and microstructural evolution. Observation from the tensile tests indicated a strong dependence of flow stress on deformation temperature and strain rates. At a constant strain rate, flow stress decreased as the temperature increased, while at a constant deformation temperature, flow stress decreased with decreasing strain rates. The strain rate sensitivity varies from 0.01 to 0.25, suggesting a diffusion-controlled dislocation climb mechanism. Dynamic recrystallization (DRX) initiation was observed at 250 °C and a strain rate of 0.001s−1, characterized by the formation of necklace-type grains with low pole intensity. Predominantly, the DRX softening mechanism, including continuous dynamic recrystallization (CDRX) and discontinuous dynamic recrystallization (DDRX), was observed at 350 °C and 300 °C for a strain rate of 0.001s−1. Fracture morphology analysis of the tested samples indicated a micro-void coalescence mechanism. Equiaxed dimples were found at 350 °C and a strain rate of 0.001s−1, while oval-shaped dimples were observed at 300 °C and 0.1s−1. A strain-compensated Arrhenius model was incorporated to estimate the flow stress prediction for hardening and softening regions. Statistical parameters such as the average absolute relative error (AARE = 13.50) and coefficient of determination (R = 0.97) were calculated. Good agreement between experimental and prediction stresses was achieved at a 0.001s−1 strain rate for all deformation temperatures.